2000
DOI: 10.1088/0953-2048/13/2/303
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Bi-2212-based composites with submicrometre-grained (Sr, Ca)SnO3

Abstract: Phase assemblage was investigated in the Bi-Sr-Ca-Cu-Sn-O system at temperatures of Bi-2212 phase crystallization. It is found that the Sr 1−x Ca x SnO 3 phase (x = 0.1-0.2) is compatible with Bi-2212 as well as with Bi-2201, CuO, alkaline-earth metal cuprates and bismuthates. The solubility of Sn in Bi-2212 is limited to low values. The superconducting composites Bi-2212-(Sr, Ca)SnO 3 were prepared by melt crystallization using single precursor and mixed precursor routes. The materials consisted of Bi-2212 ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…[3][4][5][6][7][8][9] It has been found that the Pb doping at Bi site in Bi-2212 increases the c-axis conductivity by more than one order of magnitude and reduces the anisotropy. The main advantages of Bi-based systems are their layered structure and hence texturing can be easily induced in it.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9] It has been found that the Pb doping at Bi site in Bi-2212 increases the c-axis conductivity by more than one order of magnitude and reduces the anisotropy. The main advantages of Bi-based systems are their layered structure and hence texturing can be easily induced in it.…”
Section: Introductionmentioning
confidence: 99%
“…In the BSCCO system, it has some controversial results, in which Kazin et al 31 suggested that Sn reduced the magnetism in the system prepared but Li et al 44 and Seyoum et al 28 suggested that Sn increased the pinning property and the J c of the system. The authors' study showed that the pinning behaviour in Bi-2212 doped by SnO decreased as obtained by Kazin et al, 31 and the authors believed that the superconductivity of the prepared system was destroyed at low magnetic field values. Magnetisation critical current density J cmag of the whisker was calculated using the Bean model 46 and found to be 13610 3 at 5 K. We believe that Sn ions more probably incorporate into interstitial sites in the BSCCO-2212 unit cell, which can cause the blocking of the transport of carriers between Bi-O and Cu-O layer and hence decrease J c .…”
Section: Magnetic Propertiesmentioning
confidence: 99%
“…Marine et al 45 reported that Sn doped YBCO exhibited less magnetism with applied fields than that of undoped sample. In the BSCCO system, it has some controversial results, in which Kazin et al 31 suggested that Sn reduced the magnetism in the system prepared but Li et al 44 and Seyoum et al 28 suggested that Sn increased the pinning property and the J c of the system. The authors' study showed that the pinning behaviour in Bi-2212 doped by SnO decreased as obtained by Kazin et al, 31 and the authors believed that the superconductivity of the prepared system was destroyed at low magnetic field values.…”
Section: Magnetic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Die Entdeckung der blauviolett‐ bis magentafarbenen Pigmente auf Apatitbasis17) (A5(PO4)3(OH, CuOx), A = Ca, Sr, Ba) entspricht dagegen einem Treffer im Lotto: Der Apatit war als eine der wenigen Verbindungen erkannt worden, die in der Schmelze von Bismutcuprat‐Supraleitern thermodynamisch stabil sind, und sollte feinteilig in das supraleitende Material eingebracht werden, um so die Flussschläuche zu verankern und damit die Stromtragfähigkeit des Supraleiters zu erhöhen 18. (Bei Supraleitern 2.…”
Section: Materialsynthese Heute: Explorativ Und Aleatorischunclassified